The Historical Space-Time Continuum as an Anthropological Phenomenon - Yu. L. Sirotkin (Дискурс, 2022)
Introduction. The problem of human being as a subject of the historical space-time continuum is actualized by social transformations and the change of types of rationality. The anthropological nature of space-time determines the interest in reflection on human being as a historical individual. We could note an increased interest in spatial and temporal problems in Russian philosophical thought in the realities of the 20th century. The perception of historical time in its daily eventfulness brings us closer to understanding the fate of society in this period of Russian history that cannot be unambiguously assessed.Methodology and sources. The author relied on the provisions of philosophical anthropology about the human dimension of historical time and space. The initial basis of the research was the provisions of the author's concept of the unity of a human being and the space-time continuum. The anthropological content of historical space-time analytics predetermined the use of systemic, culturological and axiological approaches. The system approach has determined the application of source studies, phenomenological and hermeneutic analysis of the studied phenomena.Results and discussion. The importance of anthropocentrism for understanding historical individuality is substantiated. The author made an attempt to overcome the extremes of the anthropocentric and progressive models of the historical process on the basis of the unity of anthropocentrism, cultural centrism and sociocentrism. History is revealed as the time and space of self-realization of its subjects. The understanding of history is derived from a person's ability to experience and organize events. Also in the article is stated the necessity of incorporation of personal time and private space into the historical process as its constructs. It is shown that the knowledge of history is the result of the identification of I and We.Conclusion. The author reveals the thesis about human being as a historical personality. The anthropological nature of historical space-time determines the meanings, contributes to the ordering of everyday events by the subjects of history, provides an opportunity to determine the vector of cognition of history.